Comparison of the Implementation of the 1994 Curriculum and the 2006 Curriculum in History Subjects: A Case Study in Senior High Schools (SMA) in Magelang - Suryawan, Muhamad Jufri; Romadi, Romadi (Universitas Negeri Semarang, 2021)
The research aimed to compare History study material based on Curriculum 1994 and Curriculum 2006 in Senior High Schools in Magelang Regency, to compare the method or learning models of History learning in Senior High Schools in Magelang Regency, to compare learning media for History in Senior High Schools in Magelang Regency, and to compare the evaluation of History learning in Senior High School in Magelang Regency. The object of the research was three senior high schools in Magelang Regency. The research used a descriptive qualitative approach and case study research design. Data collection methods were observation, interview, and documentation. The data analysis technique was interactive and consisted of data reduction, presentation, and conclusion. The research shows that History study notes, History learning method, History learning media, and History learning evaluation of Curriculum 1994 and Curriculum 2006 are significantly different during the curriculum implementation in three senior high schools as the location of the study, that is, SMA Muhammadiyah 1 Muntilan, SMA Negeri 1 Grabag, and SMA Pangudi Luhur Van Lith Muntilan.